Victimology - Doerner, William G., 1949-; Lab, Steven P. (New York ; London : Routledge Taylor & Francis Group, 2021)
"This book covers the scope of crime victims' suffering in the U.S., offering a history of victims and the measurement of victimization, an explanation of the victim's role in the criminal justice process, and a recounting of the issues crime victims face as a result of crime and the criminal justice process. Doerner and Lab, both well-regarded scholars, write compellingly about how the current criminal's justice system can be transformed into a victim's justice system. Theory is woven together with the description of each topic, and specific examples illustrate each point. The book goes on to address the full impact of victimization, and a final section details specific types of victimization, ranging from violent crimes, including child and elder abuse, to property crime, to crime in the school and in the workplace. The authors explain how obstacles hinder the pursuit of justice, and provide significant policy and programming suggestions to render the system more victim-friendly. Appropriate for undergraduate as well as early graduate students in Victimology courses in Criminology, Criminal Justice, Sociology, and Justice Studies programs, this book offers instructor's aides with test bank and PowerPoint lecture slides as well as a companion site with student resources"--
Definition and scope -- The scope of victimology -- Measuring criminal victimization -- Addressing the impact of victimization -- The costs of victimization -- Remedying the impact of victimization -- Restorative justice -- Victim rights -- Types of victimization -- Traditional crimes -- Sexual battery -- Intimate partner violence -- Child maltreatment -- Crime and then elderly -- Hate crime victimization -- Victimization at school -- Victimization at work -- References -- Index.
Includes bibliographical references and index.
Keywords: Victims of crimes; Criminal statistics